Our changing environment. Grade K STEM road map for elementary school - Johnson, Carla C., 1969-; Walton, Janet B., 1968-; Peters-Burton, Erin E. (New York, NY : Routledge, 2022)
What if you could challenge your kindergartners to come up with a way toreduce human impact on the environment? With this volume in the STEM Road Map Curriculum Series, you can! Our Changing Environment outlines a journey that will steer your students toward authentic problem solving while grounding them in integrated STEM disciplines. Like the other volumes in the series, this book is designed to meet the growing need to infuse real-world learning into K-12 classrooms. This interdisciplinary, three-lesson module uses project- and problem-based learning to help students investigate the environment around them, with a focus on ways that humans can impact the environment. Working in teams, students will investigate various types of human impact on the environment (including pollution, littering, and habitat destruction), will participate in a classroom recycling program, and will explore the engineering design process as they devise ways to repurpose waste materials. To support this goal, students will do the following: Identify human impacts on the environment. Identify technological advances and tools that scientists use to learn about the changing environment, and use technology to gather data. Explain, discuss, and express concepts about the environment through development and design of a publication to report their scientific findings about the environment around the school. Chart and understand local weather patterns, and make connections between weather conditions and their observations of the environment. Identify and demonstrate recycling practices, including sorting materials and tracking amounts of materials recycled, and participate in a class recycling program. The STEM Road Map Curriculum Series is anchored in the Next Generation Science Standards, the Common Core State Standards, and the Framework for 21st Century Learning. In-depth and flexible, Our Changing Environment can be used as a whole unit or in part to meet the needs of districts, schools, and teachers who are charting a course toward an integrated STEM approach.
Keywords: Environmental protection; EDUCATION / Teaching Methods & Materials / Science & Technology; EDUCATION / Teaching Methods & Materials / Mathematics; EDUCATION / Curricula